A study on the condition of public food court’s facilities under the management of local authority / Mohd Rahimi A. Rahman - A. Rahman, Mohd Rahimi (Faculty of Architecture, Planning and Surveying, 2010)
Increased of population are follow by growing needs and demand of community which caused Local Authority to play their role to fulfil of this demand by provides a complete facilities and utilities for the community at one area. Therefore many facilities provides by Local Authority such as bus stop, road, playground, park and also food court. Lately, there is always reported at news paper or television on the public food court problem such as building structure damage, poor cleanliness level, dysfunctional of services and facilities by food court user and tenants. And, ironically, these report mostly involved public food courts manage by Local Authority and why this problem occur involved Local Authority has to investigate. Therefore this research is emphasize to study public food court building and facilities condition which manage under the Local Authority to know the actual condition of food court condition, in order to find out user satisfaction and effectiveness of Local Authority maintenance management practice. To find out and gather an information related to this research, an interview and questionnaire are use as research methodology to gain a primary and secondary data at four selected food court building, which each of it manage under different Local Authority at different area to know the current food court building condition, current maintenance management practice by Local Authority and user satisfaction level on current food court building condition.